Managing cardiotoxicity associated with immune checkpoint inhibitors. Issue 1 (March 2019) - Upadhrasta, Sireesha; Elias, Hadi; Patel, Keval; Zheng, Lei
Abstract: Immuno-oncology is a fast evolving field of cancer therapy and immune checkpoint inhibitors (ICIs) are clearly a breakthrough in this field. Cardiotoxicity with conventional anti-cancer therapies has been well studied in the past and clear guidelines for management of these side effects are available in the literature. However, cardiotoxicity with novel agents such as ICIs has been fairly under-reported and/or underestimated and we are yet to formulate clear guidelines for management of these rare side effects. In the last few years, there has been an overall increase in the number of cases of cardiotoxicity related to ICIs. In this literature review, we describe the mechanism of action of the most widely used ICIs and their related cardiotoxicities. The increase in number of case reports about the potential of cardiotoxicities with these novel agents clearly indicates the need for a new insight into the field of cardio-immuno-oncology.